In-utero pancreatic cyst with postnatal resolution - Joseph G. Brungardt; Kurt P. Schropp (Journal of Pediatric Surgery Case Reports, 2020)
Prenatal imaging continues to improve and with it, the detection of abnormal findings. Pancreatic cysts in the newborn are a rare clinical entity, most often managed by close monitoring and surgical resection if they become symptomatic or once the child has grown. We followed such a lesion with serial imaging and found it to resolve spontaneously by four months of age. Keywords: Congenital, Pancreatic, Cyst, Prenatal, Imaging